2012
DOI: 10.1186/1472-6963-12-66
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for participation in a public health insurance program among residents of urban slums in Nairobi, Kenya: results from a cross-sectional survey

Abstract: BackgroundThe government of Kenya is making plans to implement a social health insurance program by transforming the National Hospital Insurance Fund (NHIF) into a universal health coverage program. This paper examines the determinants associated with participation in the NHIF among residents of urban slums in Nairobi city.MethodsThe study used data from the Nairobi Urban Health and Demographic Surveillance System in two slums in Nairobi city, where a total of about 60,000 individuals living in approximately 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
66
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 22 publications
18
66
2
3
Order By: Relevance
“…The observed poor participation in the NHIF scheme can be explained by unmet health care needs for NHIF members, especially when members of the NHIF scheme still have high out of pocket expenditure like costs of travel to accredited health facilities, buying drugs like nonmembers of the scheme and inflexible scheme design features such as strict datelines to remit contributions. This finding corroborates with findings of a similar study findings by Kimani et al [18] in which he reported that NHIF scheme design features were an impediment to enrolment by people living in the slums of Nairobi, Kenya.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The observed poor participation in the NHIF scheme can be explained by unmet health care needs for NHIF members, especially when members of the NHIF scheme still have high out of pocket expenditure like costs of travel to accredited health facilities, buying drugs like nonmembers of the scheme and inflexible scheme design features such as strict datelines to remit contributions. This finding corroborates with findings of a similar study findings by Kimani et al [18] in which he reported that NHIF scheme design features were an impediment to enrolment by people living in the slums of Nairobi, Kenya.…”
Section: Discussionsupporting
confidence: 83%
“…Poor participation by people in the informal sector in scheme has been blamed on the difficulties they face. People in the informal sector face difficulties of low and irregular incomes; this makes them unable to make timely contributions [18]. People in the informal sector also face difficulties created by inflexible scheme design features such as penalties, inflexible payment schedules, non-portability of scheme services, cumbersome enrolment and contribution procedures [27].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with findings in some previous studies. 1,24 Earlier works, 34,44 have made useful suggestions about technical design of health insurance such as frequency and amount of contribution that will suit different socioeconomic groups of people. Also innovative ways of fund-raising at the domestic level especially on goods purchased and services sought by the better -off in the society as a source of revenue collection to help the poor and the needy for a sustainable health-care financing scheme have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in this study among adults aged 40 to 60 years, hypertension prevalence was 25.6% in the slums of Nairobi: 58.9% of men were not aware of their hypertension status, 28.2% of women were not aware and only 50% of women and 30% of men had controlled blood pressure [10]. Kimani et al, previously reported high levels of catastrophic health expenditure among slum residents with up to 90% of the population not accessing any form of health insurance [11]. Overweight and obesity are largely preventable.…”
Section: Introductionmentioning
confidence: 99%